Czech Equivalents of English Gerund in Fiction - Vrtalová, Jana (Univerzita Pardubice, 2014)
The bachelor thesis focuses on the occurrence of the English gerund in relation to its syntactic functions within fictional literature and the great deal of the present paper is also concerned with the possible Czech translation equivalents. The present paper is corpus-based, there are selected texts of the English written prose analyzed and compared with their Czech translations.
České ekvivalenty anglického gerundia v umělecké literatuře
Keywords: neurčité slovesné tvary; ing tvary; gerundium; české ekvivalenty; fikce; non-finites; ing forms; gerund; Czech equivalents; fiction